Plant Bioactive Constituents Play a Potential Role in the Treatment of Spasticity in Multiple Sclerosis: A Review - Neelamma, G.; Nagarani, B.; Mangamma, K. (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
Multiple sclerosis (MS) is a chronic, disabling disease of the central nervous system (CNS) that strikes in early adulthood. Despite several US FDA-approved medications, the treatment options for multiple sclerosis are limited. The main objective of this study was focused on plant bioactive constituents play an important role in the treatment of spasticity in Multiple sclerosis disease. Many people with MS look into herbal treatments to help them control their MS and treat their symptoms. According to surveys, up to 70-80 percent of people with MS have tried plant products or bioactive compounds for their MS. Patients with MS who use herbal products may open up new avenues for research. Diet, omega-3 fatty acids, and antioxidants are the most commonly used phytotherapies. Bioactive plant compounds such as flavonoids, vitamin-c, lipoic acid, and vitamin D supplementation, among others, were found to be the most promising anti-inflammatory and neuroprotective agents in both relapsing and progressive forms of MS. Polyphenols, terpenes, alkaloids, anthocyanidine glycosides, plant amines, volatile oils, and other natural compounds will play an important role in the treatment of multiple sclerosis in the future.